2018
DOI: 10.1016/j.jpurol.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Has the robot caught up? National trends in utilization, perioperative outcomes, and cost for open, laparoscopic, and robotic pediatric pyeloplasty in the United States from 2003 to 2015

Abstract: Summary Introduction Since 2010, there have been few new data comparing perioperative outcomes and cost between open (OP) and robotic pyeloplasty (RP). In a post-adoption era, the value of RP may be converging with that of OP. Objective To 1) characterize national trends in pyeloplasty utilization through 2015, 2) compare adjusted outcomes and median costs between OP and RP, and 3) determine the primary cost drivers for each procedure. Study design We performed a retrospective cohort study using the Premi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 39 publications
(45 reference statements)
3
61
1
1
Order By: Relevance
“…Possible reasons for the underrepresentation of RP in our cohort include a limited availability of the robot, higher costs, and larger trocar incisions compared with conventional laparoscopy in Germany. [16][17][18] In line with reports from others, girls underwent minimal invasive pyeloplasty more often than boys did. 19,20 The reasons for this finding remain unclear since the individual steps of pyeloplasty do not differ between males and females.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Possible reasons for the underrepresentation of RP in our cohort include a limited availability of the robot, higher costs, and larger trocar incisions compared with conventional laparoscopy in Germany. [16][17][18] In line with reports from others, girls underwent minimal invasive pyeloplasty more often than boys did. 19,20 The reasons for this finding remain unclear since the individual steps of pyeloplasty do not differ between males and females.…”
Section: Discussionsupporting
confidence: 86%
“…15 Since the introduction of laparoscopy for the treatment of UPJO in 1995, the number of LP slightly increased from around 2% in 2002 to only 10% in 2006 in the United States 3,8,12 However, the number of pediatric RP markedly increased and accounted for 40% of all pyeloplasties in 2015 according to a retrospective cohort study on a nationally representative sample of the US hospitalizations between 2003 and 2015. 16 Hence, the moderate increase in LP might be attributed to the steep increase in RP in the United States. Possible reasons for the underrepresentation of RP in our cohort include a limited availability of the robot, higher costs, and larger trocar incisions compared with conventional laparoscopy in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal evaluation of practice patterns across the US showed that in 2003, 10 years after being first described, laparoscopic pyeloplasty only accounted for <20 % of the pyeloplasties performed in patients aged 13-18 years. In contrast, ten years after robotic pyeloplasty was introduced in 2015, >80% of pyeloplasties were being performed robotically in this same age group in the United States (5). This study reinforces the sentiment that robotic assisted technique is more readily adoptable and has a more favorable learning curve compared to standard laparoscopy.…”
Section: Introductionsupporting
confidence: 64%
“…As previously mentioned, the popularity of robotic pyeloplasty rose quickly and is now the gold standard for adolescent patients across the United States. In patients between 1-12 years of age, it is becoming the procedure of choice and in 2015, >40% of these patients were done robotically (5). In infants (<1 year of age), the use of robotic technique remains controversial, despite multiple reports showing the feasibility and excellent outcomes comparable to open surgery (6).…”
Section: Robotic Pyeloplastymentioning
confidence: 99%
“…However, this growth was mainly in children and adolescents. While 40% of pyeloplasties in children and adolescents in 2015 were performed robotically, 85% of infant cases were still performed via an open approach (72). Infant patients accounted for 2% and 19% of all robotic and laparoscopic pyeloplasties performed (73), but these trends are likely to change as more surgeons are trained in minimally invasive approaches.…”
Section: Surgical Treatment Of Upjo In the Infant Patientmentioning
confidence: 99%